Single-molecule multiparameter fluorescence spectroscopy reveals directional MutS binding to mismatched bases in DNA - Cristovao, Michele; Sisamakis, Evangelos; Hingorani, Manju M.; Marx, Andreas D.; Jung, Caroline P.; Rothwell, Paul J.; Seidel, Claus A. M.; Friedhoff, Peter; Justus Liebig University Giessen (My University, 2012)
Mismatch repair (MMR) corrects replication errors such as mismatched bases and loops in DNA. The evolutionarily conserved dimeric MMR protein MutS recognizes mismatches by stacking a phenylalanine of one subunit against one base of the mismatched pair. In all crystal structures of G:T mismatch-bound MutS, phenylalanine is stacked against thymine. To explore whether these structures reflect directional mismatch recognition by MutS, we monitored the orientation of Escherichia coli MutS binding to mismatches by FRET and anisotropy with steady state, pre-steady state and single-molecule multiparameter fluorescence measurements in a solution. The results confirm that specifically bound MutS bends DNA at the mismatch. We found additional MutS mismatch complexes with distinct conformations that may have functional relevance in MMR. The analysis of individual binding events reveal significant bias in MutS orientation on asymmetric mismatches (G:T versus T:G, A:C versus C:A), but not on symmetric mismatches (G:G). When MutS is blocked from binding a mismatch in the preferred orientation by positioning asymmetric mismatches near the ends of linear DNA substrates, its ability to authorize subsequent steps of MMR, such as MutH endonuclease activation, is almost abolished. These findings shed light on prerequisites for MutS interactions with other MMR proteins for repairing the appropriate DNA strand.
Keywords: dna mismatch repair (MMR); MutS; asymmetric mismatches; ddc:570